PENGARUH KEAKTIFAN MENGIKUTI PROGRAM ASRAMA, KUALITAS PERGAULAN TEMAN SEBAYA, DAN DUKUNGAN ORANG TUA TERHADAP AKHLAK MAHASISWA UNIRES UMY - Muflih, Muhammad Irhas; Iman, Marsudi (JIEGC Journal of Islamic Education Guidance and Counselling, 2022)
The purposes of the study are 1) to find out the dormitory programs for students of UNIRES, 2) to examine the peer relationship of UNIRES students, 3) to identify the parental support of UNIRES students, 4) to explain the morals of UNIRES students, 5) to find out the effect of the dormitory program, peer relationship, and parental support on the morals of UNIRES students. This type of research applied a quantitative multiple regression model approach. The population consisted of male and female residents with a total of 200 UNIRES UMY students. Samples were taken by 20% of the population or about 40 residents consisting of 16 males and 24 females. Data collection techniques used were questionnaires, observation, documentation, and interviews. After the data was obtained, it was analysed using the multiple regression test. The results obtained from the study showed that there is a positive and significant effect of actively participating in the dormitory program, the quality of peer relationship, and the parental support on the morals of UNIRES UMY students, indicated by the magnitude of the correlation (R) in the amount of 0.777 from which the coefficient of determination was obtained (R square) in the amount of 0.604 or equal to 60.4%.